Strategi Pemasaran Sawi Pakcoy (Brassica Rapa Chinensis) pada Anggota Kelompok Tani Pemuda Makmur di Desa Tiang Tara - Ali, Rafli Dwifaqih Syechan; Agustina, Fournita; Sitorus, Rositar (Universitas Galuh, 2024)
This study aims to analyze the marketing strategy of pakcoy mustard in members of the prosperous youth farmer group in Tiang Tara Village. Data were collected in October 2024 in Tiang Tara Village. The sampling method used was purposive sampling with a sample size of 16 respondents. Data analysis using the IFE matrix and EFE matrix then analyzed using the SWOT matrix, after which the decision-making stage uses QSPM. The results showed that the strategies that can be carried out by members of the prosperous youth farmer group are fifteen alternative strategies based on SWOT analysis. From the results of the SWOT cartesian matrix diagram, the company's position is in quadrant 2, meaning that the strategy that must be applied is to use strengths to take advantage of long-term opportunities by means of a diversification strategy (product / market). The most attractive and prioritized alternative strategy obtained using the QSPM matrix is to maintain product quality and service to make consumers loyal with an STAS of 6.28. The second strategy is to continuously innovate in terms of product models and functions such as packaging etc. at an appropriate price with a score of 5.78. The third strategy is to carry out good cooperation to satisfy consumers so that consumers are loyal with a score of 5.12. And the last strategy is to monitor the fluctuations in the rupiah exchange rate, fuel prices which affect the price of raw materials with a score of 3.28.